TINGKAT PREFERENSI KEPUASAN MASYARAKAT ATAS PELAYANAN YANG DIBERIKAN OLEH PEMERINTAH KELURAHAN CIPONDOH MAKMUR - Doddy Mulyono (Batara Wisnu : Indonesian Journal of Community Services, 2021)
The government is basically a public organization (society) whose job it is to meet the interests and needs of society. Therefore, the performance of government organizations can be said to either be measured by the satisfaction or dissatisfaction of the community with the services they receive from these government organizations. Thus the community's satisfaction in the services provided by government officials in a government institution is an organizational demand and a separate achievement that can be used as an institution for the institution concerned. So that to get the quality of public satisfaction, it is necessary to establish public service management. There are several things that make public service management very important, it is necessary to commit all parties and the institution itself to standardize services and accurate management strategies in providing quality services to the community